IMPROVED NARRATIVE WRITING SKILLS BY APPLLYNG THE COOPERATIVE LEARNING MODEL CONCEPT SENTENCE TYPE WITH SERIES PICTURE MEDIA - Linda Margiyani; Rukayah Rukayah; Hadi Mulyono (Universitas Sebelas Maret, 2018)
The purpose of this research is to improve narrative writing skill in third grade students of State Primary School of Mangkuyudan 02 Surakarta through the application of cooperative learning model of Concept Sentence type with picture series media. The type of this research is classroom action research held in three cycles. The subject of this research are teacher and 27 students in the third grade of State Primary School of Mangkuyudan 02 Surakarta in the academic year 2017/2018. The data collecting by interview, observation, test, and document review. The data validity technique of this reseach is content validity, triangulation of source and technique. The data analysis using descriptive comparative technique and interactive analysis model Miles Huberman. The conclusion of this research is cooperative learning model Concept Sentence type with series picture media can improve the writing narrative composition.